Chaucer's Pardoner's Prologue and Tale : An Annotated Bibliography, 1900-1995 - Sutton, Marilyn, 1944- (Book collections on Project MUSE., 2000)
The Pardoner's Tale is unique among the Canterbury Tales in that it showcases a character who also makes several other appearances throughout the Tales. One of only three pilgrims to be given a full-length prologue by Chaucer, the Pardoner takes on a dramatic force unequaled among the pilgrims. A research tool for specialist and graduate student alike, this volume on Chaucer's Pardoner's Prologue and Tale offers an exhaustive collection of material from the period 1900 to 1995, abstracting and cross-referencing book-length and chapter-length studies, sections of books and chapters, articles, portions of articles, notes, extensive commentary in editions, and representative study guides. There are separate sections for editions and translations; bibliographies, indexes, studies of the manuscript, and textual studies; sources, analogues, and influences for the Pardoner's Prologue and Tale; the Pardoner portrait in the General Prologue; studies of the Pardoner's interruption of the Wife of Bath, the wordes of the Hoost to the Phisicien and the Pardoner; the Pardoner's Prologue; and The Pardoner's Tale.The Chaucer Bibliographies are designed to encompass a complete listing and assessment of scholarship and criticism on the writings of Geoffrey Chaucer, his life, times, and historical context.